(untitled) (Medicine Today, 2020)
Introduction:The aim of the present study was to determine electroencephalographic factors associated with poorly controlled epilepsy. Materials and Methods: This retrospective study was performed from January 2007 to December 2008 at Paediatric Neurology outpatient department in Bangabandhu Sheikh Mujib Medical University, Dhaka, among the children with epilepsy of 7 months to 15 years age who had history of at least 6 months treatment with rational antiepileptic drugs daily with adequate compliance. There were two groups of patients; group 1, consisted of 50 poorly controlled epilepsy patients and group 2, comprised 50 well-controlled epilepsy patients. We retrospectively reviewed EEGs and medical records from these children. Features of initial EEGs findings were compared between the two groups. Results: Significant electroencephalographic predictors of poorly controlled epilepsy were: abnormal initial EEG (p=0.025), EEG background abnormality (p<0.001), frequent sharp wave/spike (p<0.001) and hypsarrhythmia (p=0.046). No significant difference was noticed between the two groups in respect to the location of spikes/ sharp waves. With multiple logistic regression, independent predictors of poor seizure control were EEG background abnormality and frequent sharp wave/spike. Conclusion: The study showed several Electroencehalographic factors that can be identified early in the course of childhood epilepsy which can predict development of poor seizure control. Knowledge of these factors will help us to discriminate our patients and pay more attention to those at risk of developing poorly controlled epilepsy. Medicine Today 2020 Vol.32(1): 15-20